Residual Stress and Biaxial Strength in Sc2O3–CeO2–ZrO2/Y2O3–ZrO2 Layered Electrolytes. Issue 6 (16th September 2013) - Chen, Y.; Aman, A.; Lugovy, M.; Orlovskaya, N.; Wang, S.; Huang, X.; Graule, T.; Kuebler, J.
Abstract Multi‐layered (Y2O3)0.08(ZrO2)0.92/(Sc2O3)0.1(CeO2)0.01‐(ZrO2)0.89(YSZ/SCSZ) electrolytes have been designed, so that the inner SCSZ layers provided superior ionic conductivity and the outer YSZ skin layers maintained good chemical and phase stability. Due to the mismatch of coefficients of thermal expansion between layers of different compositions, the thermal residual stresses were generated. The theoretical residual stress and strain were calculated for different thickness ratios of the electrolytes. In order to study the residual stress effect on the mechanical properties, the biaxial flexure tests of electrolytes with various layered designs were performed via a ring‐on‐ring method at room temperature and 800 °C. The maximum principal stress at the fracture indicated improved flexure strength in the electrolytes with layered designs at both temperatures. It is believed to be the result of the residual compressive stress in the outer YSZ layer. In addition, the Weibull statistics of the stress at the fracture at room temperature was studied, and the values of residual stress presented at the outer layer were well verified.